2019
DOI: 10.1016/j.trci.2019.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Alzheimer's disease who carry the APOE ε4 allele benefit more from physical exercise

Abstract: Introduction Our group has completed an exercise study of 200 patients with mild Alzheimer's disease. We found improvements in cognitive, neuropsychiatric, and physical measures in the participants who adhered to the protocol. Epidemiological studies in healthy elderly suggest that exercise preserves cognitive and physical abilities to a higher extent in AP OE ε4 carriers. Methods In this post hoc subgroup analysis study, we inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 48 publications
1
57
3
Order By: Relevance
“…On the contrary, carriers of APOE ε4 showed less modulation of the lipid profile after exercise when compared to ε4 non-carriers. This is somewhat surprising as the same cohort of APOE ε4 carriers benefitted the most from exercise regarding physical outcomes such as walking speed, endurance, and overall fitness (Jensen et al, 2019). Still, it must be stressed that none of these results are statistically significant, and that the number of patients who were ε4/ε4 carriers was low.…”
Section: Discussionmentioning
confidence: 97%
“…On the contrary, carriers of APOE ε4 showed less modulation of the lipid profile after exercise when compared to ε4 non-carriers. This is somewhat surprising as the same cohort of APOE ε4 carriers benefitted the most from exercise regarding physical outcomes such as walking speed, endurance, and overall fitness (Jensen et al, 2019). Still, it must be stressed that none of these results are statistically significant, and that the number of patients who were ε4/ε4 carriers was low.…”
Section: Discussionmentioning
confidence: 97%
“…However, this study did not report how many of these sedentary APOE4 carriers went on to develop actual AD-type dementia. A more recent study with 200 individuals diagnosed with mild AD addressed this issue, examining if exercise held any cognitive or physical improvements for APOE4 carriers [175]. The data did support that exercise intervention improved cognitive function, and was found to be more beneficial to APOE4 carriers.…”
Section: Exercisementioning
confidence: 98%
“…The APOE ε4 allele is considered as the most significant genetic risk factor that may lead to vascular damage and impaired cholesterol transport. A recent study revealed that APOE ε4 allele-carrying patients benefitted more from PA intervention than noncarriers in terms of cognitive and neuropsychiatric functions as well as physical measures (Jensen et al, 2019b). The second is associated with the modulation of neuroinflammation in AD.…”
Section: Physical Activitymentioning
confidence: 99%